Strategy for Creative Economy, and Vitality in Agriculture and Rural District - 박준기 (KREI, 2013)
The Korean government announced the ‘Scheme for creative economy-plan for creating a creative economy eco-system jointly with related ministries on June 4 this year. This scheme has 3 goals of creating new jobs and markets, enhancing global leadership with creative economy in the world, and implementing the society where creativity is respected and demonstrated. Korea’s and global economic depression continues to result in low added value from agriculture and low farmer’s income to expand the income gap between urban workers and farmers. People expect great outcome from the strategy for creative economy suggested by Park’s government. The strategy for growth through the base of creative economy will be a scheme for new jobs and enhanced added values by consolidating innovative ideas from agriculture and rural districts into natural resources, science and technology. The sixth industry of agriculture is one of important strategies for enhancing added values and creating new jobs through integration and consolidation between primary, secondary and tertiary industries by connecting processing, distribution and services centered at production of agricultural products. Added values are enhanced by processing raw agricultural products produced by farmers. Stable distribution bases are constructed to be beneficial to consumers to enhance surplus values between producers and consumers and will contribute to new jobs in the process of creating added values and connection between industries. Recent integration of agriculture with ICT results in changing agriculture to a high value-added integration industry. Creative combination with ICT in all processes of agricultural product production, distribution and consumption enables smart agriculture to be shaped with precise production, efficient distribution and streamlined management. Agriculture integrated with life engineering becomes a new industry ‘life industry’, and will develop to be centered at the value of humans to contribute to consumers’ healthy living and welfare. For creative economy in agriculture and rural districts, it is necessary to support creative human resources, to improve investment in and loans for R&D, to build a governance system for integration, cooperation and solidarity, to build a base for creative economy (regulation reformation, system overhaul, vitalized venture capital investment, expansion of management recovery system).